Analisis Usahatani Jamur Tiram Melalui Media Limbah Serbuk Gergaji Di Desa Sokkolia Kecamatan Bontomarannu Kabupaten Gowa (Studi Kasus : CV. Surya Muda Mandiri) - Dina, Annisa Asro; Zulkifli, Zulkifli; Syafruddin, Reni Fatmasari (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the costs, revenues, income, and business feasibility of oyster mushroom (Pleurotus ostreatus) cultivation run by CV. Surya Muda Mandiri. Oyster mushrooms are one of the agricultural commodities with high economic value with promising market prospects, both locally and nationally. The research method used is a case study with a quantitative approach. Data were obtained through direct observation and interviews with business actors. One important aspect in this cultivation activity is the utilization of sawdust waste as the main planting medium. The use of sawdust can reduce production costs and maximize the utilization of resources from wood processing industry waste. The results showed that the oyster mushroom business at CV. Surya Muda Mandiri generated income of IDR 4.211.562 per planting season for 4 months, with a total production cost of IDR 18.288.438and total revenue reaching IDR 22,500,000. The R/C ratio value of 1.23 indicates that this business is feasible to run and financially profitable. The utilization of sawdust waste provides added value in production efficiency and raw material management.